Evaluation of Stabilized Chlorine Dioxide in Terms of Antimicrobial Activity and Dentin Bond Strength - Kalay, Tugba S.; Kara, Yakup; Karaoglu, Sengul Alpay; Kolayli, Sevgi (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: Antimicrobial agents are recommended for disinfection of the cavity following mechanical dental caries removal prior to application of restorative material. There is limited information about stabilized Chlorine Dioxide (ClO2) as a cavity disinfectant. Objectives: The objective of this study is to determine the antimicrobial activity and effect on dentin bond strength of ClO2 compared to chlorhexidine digluconate (CHX), sodium hypochlorite (NaOCl) and Ethanolic Propolis Extract (EPE). Methods: Antimicrobial activities of agents against oral pathogens (Staphylococcus aureus, Enterococcus faecalis, Streptococcus mutans, Lactobacillus acidophilus, Lactobacillus casei, Candida albicans, and Saccharomyces cerevisiae) and analyses of EPE were examined. Seventyfive mandibular third molars were sectioned, prepared and divided into five subgroups (n=15/group). Cavity disinfectants (2% CHX, 2.5% NaOCl, 30% EPE, 0.3% ClO2) were applied to etched dentin prior to adhesive and composite build-up. Shear bond strength (SBS) was evaluated with a universal testing machine at a crosshead speed of 0.5 mm/min. The SBS data were analyzed with One-way Analysis of Variance (ANOVA) and Tukey’s post-hoc test (p <0.05). The failure modes were evaluated with a stereomicroscope. Results: It was determined that the compared disinfectants were showed different inhibition zone values against oral pathogens. ClO2 exhibited the highest antimicrobial activity, followed by CHX, NaOCI and EPE, respectively. No statistically significant difference was observed in the SBS values between the disinfectant treated groups and control group. The failure modes were predominantly mixed. Conclusion: The use of 0.3% stabilized ClO2 as a cavity disinfectant agent exhibited high antimicrobial activity against oral pathogens and no adverse effects on SBS to etched dentin.
Keywords: antimicrobial activity